PROSES PENANGANAN IKAN HASIL TANGKAPAN DAN KERUSAKAN FISIK IKAN HASIL TANGKAPAN UTAMA POLE AND LINE PADA KM. INKAMINA 523 - Putri, Elsari Tanjung; Manengkey, Jenny I (JURNAL BLUEFIN FISHERIES, 2023)
The main catch of pole and line is skipjack tuna. There are several factors that influence the derivation in fish quality and post-catch fish damage, including inadequate facilities, fishing techniques and fish handling processes that is not in accordance with procedures. This study aims to explain the process of fish handling on board and identify main catch fish physical damage. The research method is observing of fish handling activities on board, recording the type and amount of the catch and identifying the physical damage to the catch during the fishing trip. The results showed that the stages of the fish handling on board consist of fish watering, sorting, washing, ice preparation, and storing the catch in fish hold. Fish handling on FV. Inkamina 523 has applied the principles of quick, careful, clean and cold chain. In fish handling activities, the ships’s crew are not equipped with work safety equipment. The main catch fish physical damage (skipjack tuna) on FV. Inkamina 523 i.e broken stomach, broken head, broken tail, broken eyes and ripped skin.